Dimension-controlled halide perovkites using templates. (August 2021) - Paul, Susmita; Ariga, Katsuhiko; Sarma, D.D.; Acharya, Somobrata
Abstract: Metal halide perovskites promise outstanding potential for a variety of optoelectronic applications. Electronic properties of the perovskites change remarkably upon changing the dimensionality owing to the change in the spatial confinement of the charge carriers, which is useful for device applications. Conventionally, metal halide perovskites are synthesized by means of hot injection (HI) and ligand assisted reprecipitation methods (LARP). However, these synthetic strategies are not well-suited yet to control the shape and spatial dimensionality of the perovskite nanocrystals/microcrystals. Advantageously, template-based synthesis creates perovskite nanocrystals/microcrystals with well-defined shape and spatial dimensionality depending on the nature of the template. Additionally, the template-based synthesis enables a ligand-free approach to realize perovskite nanocrystals/microcrystals with enhanced stability. Perovskite preparation via template-based synthesis route demonstrates the immense potential to become an alternative to the presently available synthetic techniques. This review will explore the research progress, current focus and our views on the template-based synthesis of the perovskite nanocrystals/microcrystals to reveal the immense chemical flexibility and outstanding potential to control the shape and spatial dimensionality required for optical, electronic, and energy-related applications. Graphical Abstract: ga1 Highlights: Perovskite nanocrystals with different spatial dimensionality synthesized using various templates are reviewed. Advantages of the template-based synthesis of perovskite nanocrystals over conventional synthesis routes are discussed. Uniqueness of the template-based synthesis to enhance the stability of perovskite nanocrystals is highlighted. The ability of ligand free synthesis of perovskite nanocrystals using various templates are focused. Future challenges associated with the template-based synthesis are envisioned.